Safety and Efficacy of Triple Therapeutic Targets with Rivaroxaban after Acute Myocardial Infarction Complicated by Left Ventricular Thrombi in a Case of Nonvalvular Atrial Fibrillation - Francesco Summaria; Gregory A. Sgueglia; Fabrizio D’Errico; Antonella De Santis; Fabiana Piccioni; Gaetano Gioffrè; Achille Gaspardone (Case Reports in Cardiology)
We present the complex case of a high-risk patient with nonvalvular atrial fibrillation, who experienced a non-ST elevation myocardial infarction complicated by left ventricular (LV) thrombi and underwent percutaneous coronary intervention with drug-eluting stent implantation. The patient was initially treated with short-term triple therapy including aspirin, clopidogrel, and rivaroxaban 15 mg/die. Following aspirin dropping one month after discharge, the patient continued on dual therapy with clopidogrel and rivaroxaban, and a clinical and imaging follow-up at 6 and 12 months confirmed the LV thrombi resolution, with no thromboembolic episodes and a good safety profile.